OP0156 Deciphering The in Vitro Therapeutic Potential of JAK Inhibitors in Ankylosing Spondylitis. (15th July 2016) - Hammitzsch, A.; Chen, L.; Al-Mossawi, H.; Simone, D.; Ridley, A.; Bowness, P.
Abstract : Background: In Ankylosing Spondylitis (AS) therapeutic options include blocking of TNF and IL-17, but are expensive and limited compared to other rheumatic diseases. In addition there is no convincing evidence that either of these therapies is able to block new bone formation, the hallmark of AS. Small molecule inhibitors of Janus kinases (JAK) are potent inhibitors of other inflammatory diseases including Rheumatoid Arthritis (RA), and inhibit new bone formation in murine Spondyloarthritis 1, 2 . Objectives: We evaluated the ability of 4 different JAK family inhibitors to reduce IL-17A production in vitro using blood and synovial fluid samples from patients with AS, Psoriatric Arthritis (PsA) and RA. We choose to study Tofacitinib, as it shows relative specificity to JAK3, Ruxolitinib (JAK1), CEP-33779 (JAK2) and Bayer-18 (TYK2), in order to decipher the most potent inhibitor for this disease. Methods: CD4 T cells were isolated from PBMC of AS (n=43), PsA (n=13), RA patients (n=10) and Healthy controls (HC, n=15) and stimulated for 3 days under Th17-promoting conditions in the presence of JAK inhibitors. Cytokine secretion (IL-17A for all samples, IL-17F, IL-22, GM-CSF and IFNγ for a representative subgroup) was assessed using ELISA, measured in pg/m, and expressed as relative to control. Cytotoxicity and proliferation were measured with Annexin V/7-AAD staining and CFSE dilution on Flow cytometry. TYK2 was silenced in primary human CD4 T cells with siRNA and effects were analysed using ELISA and Western Blot. Results: All JAK inhibitors tested reduced secretion of IL-17A in CD4 T cells from AS, PsA, RA patients and HC (see Fig. 1 for data on AS and HC). In a small subset of 10 AS patients Tofacitinib showed statistically significant inhibition of IL-17F, IL-22, GM-CSF and IFNγ secretion, and CEP-33779 of IL-22 and GM-CSF secretion. At the same time cytotoxicity and anti-proliferative capacity of the inhibitors was low. No correlation between inhibitory capacity of the different small molecules and clinical parameters was observed. Bayer-18 did not significantly reduce Th17 cytokine secretion, but siRNA-mediated knock down of TYK2 in primary human CD4 T cells inhibited IL-17A, IL-22 and IL-17F secretion, when knock-down efficacy exceeded 70%. Conclusions: All JAK inhibitors tested reduce IL-17A secretion from CD4 T cells in vitro. Despite the fact that our study does not address the specificity of the different JAK inhibitors, we find no clear evidence that targeting any one JAK family member is superior in reducing in vitro Th17 responses. Our siRNA knock-down data suggest that TYK2 is still a valuable target for developing new treatments in AS, even though blockade of its kinase activity was not efficacious in reducing IL-17A secretion. One explanation is that the IL-17A-inducing activity of TYK2 was not inhibited by Bayer-18 in our assays or that the scaffold function of TYK2 is more important in this pathway. References: Fleischmann R. et al, Placebo-controlled trial of tofacitinib monotherapy in rheumatoid arthritis. N Engl J Med. 2012;367(6). Lories R. et al, Tofacitinib inhibits inflammation and new bone formation in murine Spondyloarthritis but does not adversely inhibit human MSC function [abstract]. Arthritis Rheumatol. 2015;67 (suppl 10). Acknowledgement: AH was supported by DFG (Deutsche Forschungsgemeinschaft, HA-7021/1–1) and DS by SIR (Società Italiana di Reumatologia). Disclosure of Interest: None declared